Codeword averaged density evolution for distributed joint source and channel coding with decoder side information - Cen, Feng; Zhu, Fanglai (IET communications, 2014)
The authors consider applying the systematic low-density parity-check codes with the parity based approach to the lossless (or near lossless) distributed joint source channel coding (DJSCC) with the decoder side information for the non-uniform sources over the asymmetric memoryless transmission channel. By using an equivalent channel coding model, which consists of two parallel subchannels: a correlation and a transmission sub-channel, respectively, they derive the codeword averaged density evolution (DE) for the DJSCC with the decoder side information for the asymmetrically correlated non-uniform sources over the asymmetric memoryless transmission channel. A new code ensemble definition of the irregular codes is introduced to distinguish between the source and the parity variable nodes, respectively. Extensive simulations demonstrate the effectiveness of the codeword averaged DE.